From Crisis to Growth: A Digital Platform Strategy for Tanjung Lesung SEZ Using the SOAR Framework (2018-2024) - Pertiwi, Husna Putri; Raga, Ridha Azka; Wirawan, Adhitomo; Pinem, Robetmi J. (Yayasan Sinergi Kawula Muda, 2025)
Tanjung Lesung, Indonesia's first Tourism Special Economic Zone (SEZ), suffered setbacks from the 2018 tsunami and the COVID-19 pandemic. These crises led to decreased tourist visits, raising safety concerns and impacting the area’s image. Thus, this study explores the role of digital platform-based promotion in revitalizing Tanjung Lesung SEZ by assessing the effectiveness of Tanjung Lesung’s official digital channels in rebuilding its brand, enhancing engagement, and attracting visitors as well as using the SOAR (Strengths, Opportunities, Aspirations, Results) framework to develop actionable strategies that contribute to an enhanced digital marketing strategy for Tanjung Lesung. This research is a descriptive qualitative method, incorporating surveys and interviews from the Penta helix point of view and undertaking digital analytics. This study found that word-of-mouth remains a powerful tool in attracting visitors to Tanjung Lesung. Thus, the findings suggest that leveraging personal recommendations from friends and family contributes significantly to building a positive reputation. Therefore, The digital strategy encourages visitors to share their experiences online, further amplifying word-of-mouth impact and building community trust